ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PRODUK (Studi Kasus Pada PT. Simongan Plastik Factory Semarang) - Suryanto, L. Suryanto; Sutopo, Sutopo (Universitas Muhammadiyah Magelang, 2004)
This research conducted on the evidence that there were a declining trend of the quality product at PT. Simongan Plastik Factory Semarang which was proven by increased percentage of damage production. Improvement activity have been doing continously to get a good ang qualified product, by improving at all area making a quality team and also supporting from management. The research also based on the previsious researcher recommendation. There were four Quality Management Implementation contructs by previous researcher-Leadership, Employee development and empowerment, Quality system improvement and, Evaluation and process conrol are used to analiyze the significance of its influence toward product quality, and then, it will identify the most influencing construct quality. Critical review and acknowledgement with relevant literature was developed to build a model and foe hypotheses with 27 indicators that will be tested using confirmatory factor analysis and full model structural equation model (SEM) with doodness-of-fit criteria. To test the hypotheses for primary data got from interviews with 200 employes of PT. Simongan Plastik Factory, production departement, who act as the sample of his research, we used AMOS 4.0 computer statistical program for windows. According the result from confirmatory factor analysis of primary data, it show no difference between covariant matrix of sample and covariant matrix estimated from the population and the 27 indicators were significantly its latent factors. From full model SEM analysis result it show that all goodness-of-fit criteria can be achieved. Result from hypotheses test show that all hypotheses can be accepts at 1% and even at 5% level significance. And finally found that Quality system improvement has the bigger influence toward product quality of the outcomes.